Decreased HOMA-IR levels after physical exercise as a therapy to reduce insulin resistance: A systematic review - Putra, Dany Pramuno; Wibawa, Junian Cahyanto; Putro, Baskoro Nugroho (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
A sedentary lifestyle can increase metabolic diseases such as diabetes mellitus. The aim of this study was to determine how physical activity reduces insulin resistance by reducing HOMA-IR levels. This study also provides a theoretical basis for physical exercise in preventing insulin resistance in humans. For our systematic review, we searched several literature databases (PubMed, Web of Science, and ScienceDirect) for articles published in the past five years that examined physical activity and HOMA-IR. A total of 422 published papers were located using the Web of Science, Pubmed, and Science Direct databases. Ten papers that satisfied the inclusion criteria were chosen and examined for this systematic review. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) were used in this study to assess standard operating procedures. It has been demonstrated that regular exercise lowers insulin resistance by lowering HOMA-IR values. It has been proven that physical exercise is the best therapy for people with metabolic diseases, especially insulin resistance. Physical exercise has been shown to significantly reduce insulin resistance by decreasing HOMA-IR levels. Therefore, regular physical exercise is highly recommended as the best therapy for insulin resistance in humans.